PENERAPAN DONGENG INTERAKTIF DALAM MENINGKATKAN MINAT BACA PADA ANAK DI TBM SEKAR BANGBARA - Rismawati, Resti; Matin, Ahmad Ghilman; Akbar, Syahsultan Alif; Rahima, Geriya; Kharisma, Silviany; Hamdan, Ahmad (Jurnal Pengabdian Masyarakat Indonesia, 2024)
This dedication was motivated by the low interest in reading by the community, especially in the young generation of school age in the environment around TBM Sekar Bangbara. This service aims to analyze and document the application of interactive storytelling as an innovative strategy in increasing children's interest in reading at TBM Sekarbangbara. With a focus on early literacy development, this study identifies the steps of community service preparation, from determining the type of service to compiling concepts, as well as implementation stages such as the selection of fairy tales, procurement of reading books, and making property. With this activity, it is hoped that TBM Sekarbangbara can be an effective model in responding to children's literacy needs, creating a stimulating learning environment, and supporting positive development in the local community. The results of this study can contribute to further understanding of the application of interactive storytelling as a strategy to increase children's interest in reading in various community literacy centers.